Evading plant defence: Infestation of poisonous milkweed fruits (Asclepiadaceae) by the fruit fly Dacus siliqualactis (Diptera: Tephritidae). (1st December 2017) - Schneider, Michael; Wunder, Cora; Reuss, Esther; Toennes, Stefan W.; Mebs, Dietrich
Abstract: To cope with toxic metabolites plants use for defence, herbivorous insects employ various adaptive strategies. For oviposition, the fruit fly Dacus siliqualactis (Tephritidae) uses milkweed plants of the genus Gomphocarpus (Asclepiadaceae) by circumventing the plant's physical (gluey latex) and chemical (toxic cadenolides) defence. With its long, telescope-like ovipositor, the fly penetrates the exo- and endocarp of the fruit and places the eggs on the unripe seeds located in the centre of the fruit. Whereas most plant parts contain high concentrations of cardenolides such as gomphoside, calotropin/calacatin and gomphogenin, only the seeds exhibit low cardenolide levels. By surmounting physical barriers (fruit membranes, latex), the fly secures a safe environment and a latex-free food source of low toxicity for the developing larvae. One amino acid substitution (Q111V) at the cardenolide binding site of the fly's Na +, K + -ATPase was detected, but the significance of that substitution: reducing cardenolide sensitivity or not, is unclear. However, poisoning of the larvae by low levels of cardenolides is assumed to be prevented by non-resorption and excretion of the polar cardenolides, which cannot passively permeate the midgut membrane. This example of an insect-plant interaction demonstrates that by morphological and behavioural adaptation, a fruit fly manages to overcome even highly effective defence mechanisms of its host plant. Highlights: The paper describes a peculiar insect-plant relationship. A fruit fly is placing its eggs into the fruit of a poisonous plant where the larvae develop feeding on unripe seed. The fly overcomes the plant's defense mechanisms (sticky latex, toxic cardenolides) by behavioural adaptation.